Development of Interactive 3D Animation Video of the Bible Story of Cain and Abel - Rumengan, Junita Lisa Citra; Mamahit, Dringhuzen J.; Paturusi, Sary D. E. (Universitas Sam Ratulangi, 2021)
Abstract — In religious education is a teaching aimed specifically at children from infants to adolescents. In the Bible there are various stories that tell many characters from the Bible story, the stories of Cain and Abel are familiar to Christians. By utilizing the development of the animation industry, an interactive 3-dimensional video animation design of Cain and Abel was made. In this study, the MDLC (Multimedia Development Life Cycle) method was used. Based on the results of the online user evaluation, all respondents felt helped by knowing the story of God's Word, Cain and Abel. This application is also considered interesting so that it is effective in attracting interest for the Bible story of Cain and Abel. Keywords: Bible Stories; Cain and Abel; Genesis 4: 1:16; Interactive Animation Videos Abstrak — Dalam pendidikan Agama merupakan suatu pengajaran yang ditujukan secara khusus kepada anak-anak dari bayi sampai remaja. Di dalam Alkitab terdapat berbagai cerita yang menceritakan banyak tokoh cerita Alkitab, cerita Kain dan Habel sudah tidak asing bagi umat Kristiani. Dengan memanfaatkan perkembangan industri animasi dibuatlah Perancangan Video Animasi 3 Dimensi Interaktif Kain dan Habel. Pada penelitian ini digunakan metode MDLC (Multimedia Development Life Cycle). Berdasarkan hasil evaluasi pengguna yang dilakukan secara online, maka seluruh responden merasa terbantu dalam mengetahui cerita Firman Tuhan Kain dan Habel. Aplikasi ini juga dianggap menarik sehingga efektif dalam menarik minat untuk cerita Alkitab Kain dan Habel. Kata Kunci : Cerita Alkitab; Kain dan Habel; Kejadian 4 : 1-16; Video Animasi Interaktif